Synergistic pathways for health investment and economic development in China: a fuzzy-set qualitative comparative analysis - Yongqiang Wang; Yuzhuo Liu; Yulin Chai; Kexuan Chen; Shilan Yang; Xiaochen Feng; Wei Li; Yuqing Mi (Frontiers Media S.A., 2024)
BackgroundSystem coordination is an effective way to achieve high-quality development, and the debate on the interaction between health investment and economic development is still ongoing. To strengthen previous research and offer feasible advice and references for relevant stakeholders, we provide empirical evidence for exploring intersystem coordination and enhancement pathways using data from China.MethodsBased on the data published by the National Bureau of Statistics of China, the current status of the interaction and coordination between health investment and economic development in China was measured by calculating the comprehensive evaluation index, relative development degree, and coupling coordination degree. Subsequently, a fuzzy-set qualitative comparative analysis method was introduced to explore pathways for enhancing system interaction and coordination.ResultsThere are obvious inter-provincial and regional differences between health investment and economic development in China. Provinces in the west and north are lagging in economic development, while provinces in the east and south are lagging in health investment. There is a clear synergy between health investment and economic development, and there is still much room for improving the degree of coupling coordination between systems. The five conditional configurations derived from the fuzzy-set qualitative comparative analysis yield three pathways for enhancing system coordination: a health expenditure-driven path, an economic development-driven path, and a balanced health investment and economic development-driven path.ConclusionHealth expenditure is sufficient for high coordination, and the level and equity of investment in health expenditure should be improved. The gross regional product is a necessary and sufficient condition for high coordination, and consideration must be given to strengthening the regional economic support capacity. Health investment and economic development can drive the coordinated development of the system in a balanced way. This enlightens us to give full play to the positive synergy between health investment and economic development based on promoting the benign interaction of subsystems.